2014
DOI: 10.1016/j.urolonc.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on prostate cancer outcomes after radical prostatectomy

Abstract: Objective Recent studies have shown a relative risk reduction in the incidence of prostate cancer in patients taking metformin. However there are conflicting findings on the impact of metformin on established cases of prostate cancer. In this study we evaluated the impact of metformin on survival and pathological outcomes in established prostate cancer. Materials and Methods We retrospectively identified 12,052 patients who underwent radical prostatectomy (RP) between 1997 and 2010 at Mayo Clinic. Among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 25 publications
1
67
1
Order By: Relevance
“…For example, in 2013, Spratt et al published the first clinical retrospective data indicating that metformin use may improve progression free survival and PCa mortality. 26 In the present study we demonstrate no significant differences concerning pathological stage and Gleason score of different diabetic drug users in comparison to the control group. Moreover, there was no significant difference in biopsy tumor over-or under-grading.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…For example, in 2013, Spratt et al published the first clinical retrospective data indicating that metformin use may improve progression free survival and PCa mortality. 26 In the present study we demonstrate no significant differences concerning pathological stage and Gleason score of different diabetic drug users in comparison to the control group. Moreover, there was no significant difference in biopsy tumor over-or under-grading.…”
Section: Discussioncontrasting
confidence: 47%
“…30 On the other hand, two other large studies found a reduced mortality of PCa patients upon metformin use. 26,31 Although the anti-tumor effect of metformin has been observed in different types of cancers a clear mechanism of action remained elusive. To our best knowledge the present study is the first analyzing proposed molecular pathways of antidiabetic drugs in the prostate tissue of patients suffering from both PCa and DM.…”
Section: Discussionmentioning
confidence: 99%
“…Sample sizes of diabetic patients ranged from 54 to 10,309 and percentage of metformin users ranged from 17.6% to 67.6%. One study included all cancer sites (21), four on breast (25)(26)(27)(28), colon (29)(30)(31)(32), and prostate cancers each (33)(34)(35)(36), two each on pancreatic (37,38) and endometrial cancers (39,40), and one study each on ovarian (41), liver (42), laryngeal (43), and lung cancers (44).…”
Section: Resultsmentioning
confidence: 99%
“…[101][102][103][104][105][106][107][108][109] The inconsistent findings across studies may be due to their retrospective design, inappropriate comparators or the use of exposure data from sources such as medical records and automated pharmacy databases.…”
Section: Cancer Outcomesmentioning
confidence: 99%